Construction of Islamic Character Education Values Based on Local Wisdom in Culture Kasepuhan and Kanoman Palaces - U Abdullah Mu’min (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to analyze the construction of Islamic character education values based on local wisdom in the culture of the kasepuhan and kanoman palaces. The approach used in this study is qualitative with a descriptive method. The data collection techniques in this study are observation, interviews, documentation, and field notes. At the same time, the data analysis refers to the Miles and Huberman model, carried out through three steps: data reduction, data display, and conclusion. Moreover, the results of this study show that the process of constructing Islamic character education values in the culture of the Kanoman and Kasepuhan Palaces Cirebon, consisting of externalization, objectivization, and internalization of the values of local wisdom of the kanoman and kasepuhan communities that have been running at home, in schools, and in the community seems inseparable. All of them are interrelated; even though each of these institutions has a different role, each other still goes hand in shaping the character of a cultured society.